Penyuluhan Pencatatan Administrasi Keuangan dan Pencatatan Perhitungan Fisik Persediaan di PT Dwira Masagena - Tahang, Nurul Jannah; Uksi, Rafika; Vetriyani, A. Musyarrafah; Hatta, Harmiati (Santri : Journal of Student Engagement, 2025)
This community engagement program aimed to enhance the knowledge and skills of employees at PT Dwira Masagena through structured training on financial administration and inventory accounting. The company, located in the Makassar Industrial Area (KIMA), Jalan Kima Raya I Kav. B5, Makassar, has yet to implement an accounting system aligned with established theoretical standards. Financial records are currently based on estimations, and stock opname is still conducted manually. Sales performance is a key indicator of the company’s financial health, as it helps assess operational outcomes—whether the company is incurring losses or generating profits. However, reliable sales data can only be produced when financial transaction records, including inventory data, are processed accurately and in real time. This highlights the need for adequate knowledge and practical skills in inventory recording. The training was delivered using a combination of lectures, discussions, hands-on exercises, feedback sessions, and direct mentoring. The program was conducted on-site at PT Dwira Masagena. The objective was to provide relevant and applicable recommendations to company staff, tailored to their operational challenges. The intervention consisted of two main components: (1) financial recording practices encompassing five key types of financial statements and (2) training on the physical inventory accounting process. The program is expected to support improved employee performance and organizational efficiency.